(untitled) (Revista Contexto & Educação, 2023)
This article aims to analyze the theme of educational planning and management in theses and dissertations of the Post-Graduation Programs in Education (PPGE) in Brazil, in the period from 2000 to 2010, providing an overview of academic productions on this topic in the first 2000s. To reach the objective, we started from the problematization of the process of construction and consolidation of educational policy as an academic field, demonstrating the importance of expanding postgraduate programs and regional asymmetries in the number of programs, in the evaluation criteria and in the number of works about the subject under study, despite the significant representativeness in the set of studies analyzed. The achieved results point out the institutions with the highest score in Capes’ evaluation, and which have the highest academic production on the subject, are located in the Southeast and South regions, which concentrate 63% of the postgraduate programs, reiterating the inequality of knowledge production, a factor reinforced by Capes’ evaluation criteria.